Integrating Group Art Activities into School Guidance and Counseling to Foster Safe Space Education in Kindergarten: A Systematic Literature Review - Cahyo Wahyu Darmawan; Helna Fitriana (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: Psychological safety is essential in early childhood education, particularly for kindergarten children who often rely on non-verbal modes of expression to communicate their emotions. Traditional counseling approaches may not fully meet the developmental needs of young learners, highlighting the need for expressive, child-centered methods within school guidance and counseling programs. Aim: This study investigates how group art activities can foster the creation of emotionally and socially safe learning environments for kindergarten children and how these activities can be effectively integrated into school guidance and counseling practices. Method: A systematic literature review (SLR) was conducted using PRISMA guidelines to synthesize empirical research published between 2014 and 2024 on safe learning environments, expressive arts, and counseling in early childhood settings. Ten studies met the inclusion criteria and were analyzed using a thematic synthesis approach. Results and Dıscussion: The reviewed studies indicate that group art activities provide developmentally appropriate pathways for emotional expression and contribute to children's sense of psychological safety. Drawing, painting, and collage-making enable children to express emotions non-verbally, thereby reducing anxiety and facilitating emotional regulation. Collaborative artmaking also promotes social safety by enhancing peer cooperation, empathy, and supportive interactions. Furthermore, several studies have shown that integrating art into guidance and counseling sessions helps counselors identify emotional needs and build rapport with young children. Conclusion: Group art activities have the potential to enhance safe space education in kindergarten by supporting emotional expression and strengthening peer relationships within counseling contexts. However, the evidence base remains limited, and more research, particularly longitudinal and intervention-based studies, is needed to clarify the conditions under which art-based approaches most effectively promote emotional and social safety.